Drying Apple Slices in a Rotating-Tray Convective Dryer: A Study on Dehydration Characteristics and Qualitative Attributes - Hamid Ghasemkhani; Farhad Khoshnam; Mohamad Reza Kamandar (Iranian Journal of Chemical Engineering)
To improve quality attributes of the final dried product and execute a better management of the required energy, optimal process and technology it is essential to dry agri-food materials. This work is aimed at studying the dehydration characteristics and qualitative traits (color, shrinkage, rehydration ratio) of apple in a rotating-tray convective dryer with different operational variables. Furthermore, to model the dehydration curves, the usage of some well-known semi-theoretical models and artificial neural networks (ANNs) was evaluated. The drying experiments were conducted by applying the constant thickness of the samples (3 mm), different air temperatures (50‒85 °C) and flow rates (1 and 2 m s-1) as well as three tray rotating speeds (0, 6 and 12 rpm). In addition to significant (P < 0.05) reduction caused by increasing the temperature and flow rate, the process duration was considerably decreased by the increment in the tray rotating speed. The moisture diffusion inside the slices (2.708 × 10-9 ‒ 8.337 × 10-9 m2 s-1) was facilitated by increasing the values of evaluated variables. The average values for the activation energy changed from 20.47 to 23.80 kJ mol-1. In comparison with the thin layer models, artificial networks showed better performance in modeling the curves. Although drying parameters did not significantly affect the quality of studied properties, in general, higher drying air velocities and temperatures deteriorated the quality of the final products